Analisis Spirit Filantropi Islam Perspektif Aksiologi Max Scheler dalam Konteks Badan Amil Zakat Nasional: Islamic Philanthropy Morale Analysis of Max Scheler’s Axiological Perspective at National Amil Zakat Agency - Budiman, Arip; Busro, Busro; Rasyid, Ari Farizal (Jurnal Bimas Islam, 2023)
This research aims to analyze the concept of Islamic philanthropy from the perspective of Max Scheler's axiology and how the National Zakat Agency can practice Islamic philanthropic values in Indonesia. The research process uses a qualitative method with a literature study approach. The results and discussion show that the concept of Islamic philanthropy in the context of Baznas through its programs, axiologically falls into the category of spiritual and religious value hierarchies from Max Scheler's perspective. The conclusion drawn from the research is that the spirit of Islamic philanthropy has a spiritual and religious basis axiologically, especially through the implementation of Baznas programs in the distribution of zakat, infaq, and shadaqah funds. Recommendations for further research are that a more elaborate method is needed to conduct more detailed research on the strategies applied by Baznas in promoting Islamic philanthropy. This is necessary because this research is limited to only one qualitative approach.